Comparative Study of Microbiological Monitoring Results from Three Types of Sampling Methods after Gastrointestinal Endoscope Reprocessing. - Ma, Su; Feng, Lili; Jiang, Ziyi; Gao, Xian; Long, Xisha; Zhuang, Shaonan; Ding, Wenxia; Chen, Taiyao; Zhaoshen, Li; Zhang, Lingjuan; Xi, Huijun; Zhang, Hongzhi (BioMed Research International, 2019)
Objective. Compare the effects of three sampling methods on the microbiological monitoring results after reprocessing of gastrointestinal endoscopes, providing scientific basis for improving the monitoring quality of gastrointestinal endoscope cleaning and disinfection. Method. Gastrointestinal endoscopes after reprocessing were selected randomly at the gastrointestinal endoscopy center of a tertiary hospital in Shanghai from October 2018 to February 2019. The endoscopes selected were all sampled in three different methods under continuous sampling and intermittent sampling respectively. Methods used includes, the biopsy channel group (Group A), the entire channel group (Group B), and the disc brush group (Group C). Then the colony forming units (CFU/piece) were counted in the laboratory. Results. A total of 12 endoscopes were sampled by using continuous sampling approach, in which the detection rate of bacteria in disc brush group (33.3%) and entire channel group (33.3%) was higher than biopsy channel group (8.3%). Among the 12 endoscopes sampled with intermittent approach, the detection rate of bacteria from high to low was the disc brush group (50%), the entire channel group (41.7%), and the biopsy channel group (8.3%). Conclusion. Different sampling methods will lead to the difference of microbiological culture results after reprocessing of gastrointestinal endoscope, indicating that the improved sampling method is beneficial to objectively reflect the endoscope cleaning and disinfection effect, and improve the monitoring quality of endoscope disinfection.